Pengaruh Pembiasaan Shalat Dhuha Terhadap Kedisiplinan Peserta Didik Kelas VIII di Madrasah Tsanawiyah Jakarta Pusat - Fadlia, Lia; Dzakwan; Sari, Laela (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This study discusses the Effect of Dhuha Prayer Habit on the Discipline of Grade VIII Students at Madrasah Tsanawiyah, Central Jakarta. Basically, student discipline needs to be improved so that students have a sense of responsibility at school. This study focuses on finding out the magnitude of the influence of Dhuha Prayer Habituation on the discipline of Peseta Didik. This type of research is quantitative, focusing on the disclosure of the influence between variables. The population is class VIII C and class VIII D Madrasah Tsanawiyah Central Jakarta consisting of 58 students. Data was obtained through a questionnaire. Furthermore, this study was analyzed with descriptive statistics. The results of this study show that: the habit of dhuha prayer (X) has a positive and significant influence on the discipline of students (Y), the amount of influence of the habit of dhuha prayer on the discipline of students is 25.8%. Based on the findings of the study, the habit of praying dhuha has an influence on discipline in the form of order, compliance with norms, and responsibility. While the rest is explained by other variables that are not used in this study.